Analysis of Person-Job Fit and Work-Life Balance on Employee Engagement through Intrinsic Motivation in Generation Z of Private Banks in Pontianak - Margareta , Margareta; Lianto, Lianto; Ginting, Sunardi (Sekolah Tinggi Ilmu Ekonomi Amkop Makassar, 2026)
Purpose: This study examines the effect of person–job fit and work–life balance on employee engagement, with intrinsic motivation as a mediating variable among Generation Z employees in National Private Commercial Banks (BUSN) in Pontianak. Research Design and Methodology: A quantitative survey was conducted involving 170 Generation Z employees (born 1997–2012). Data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with WarpPLS 7.0. The variables measured included person–job fit, work–life balance, intrinsic motivation, and employee engagement. Findings and Discussion: The results indicate that person–job fit and work–life balance significantly and positively influence intrinsic motivation and employee engagement. Intrinsic motivation also shows a strong positive effect on employee engagement and partially mediates the relationships between person–job fit, work–life balance, and engagement. These findings suggest that psychological alignment with work and balanced life conditions stimulate internal motivation, which strengthens engagement among Generation Z employees. Implications: The study provides managerial guidance for banking institutions to design HR strategies focusing on job alignment, flexible working arrangements, and intrinsic motivation development. Future research is recommended to explore additional psychological or organizational factors influencing engagement across different industries and generational groups.